Post-Earthquake Urban Planning in Türkiye: Evaluating Disaster Refuge Systems in Hatay and Istanbul - Büşra Nur Gök; Gizem Dinç (Journal of Architectural Sciences and Applications)
Countries prone to significant earthquakes often develop disaster refuge and relief urban park systems to enhance urban open green spaces, which serve as temporary shelters for evacuation after seismic events. This paper examines the disaster refuge sites and urban open green space system in the center of Hatay following the February 6, 2023 earthquake. The findings provide insights into the resilience of Turkish cities after seismic events. Subsequently, the refuge sites and green space systems in Istanbul, a metropolis expected to experience a major earthquake, were analyzed in light of the Hatay example. Using ArcGIS, the service areas of shelter sites and urban open green spaces (within a 15-minute walking distance) were calculated and compared. Results indicate that the service areas for emergency shelters in the center of Hatay and Istanbul's Fatih district are insufficient. This highlights the need for better-planned urban open green spaces for evacuation purposes. This study makes significant contributions to improving shelter and evacuation processes after earthquakes in the fields of disaster management and urban planning.